2016
DOI: 10.1002/bdra.23505
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of nutritional and environmental factors and the risk of oral clefts in Thailand

Abstract: Our findings add to a growing body of knowledge of environmental risk factors for oral clefts from low- and middle-income countries. Our findings on liver are contradictory to prior results. Large multisite studies are needed to identify environmental and genetic risk factors for oral clefts. Birth Defects Research (Part A) 106:624-632, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Although the correlation between secondhand smoke and CMs has been a concern for several decades, different studies obtained somewhat different results . Most studies reported a significantly increased risk for cardiovascular system malformations, whereas a study by Wasserman et al did not .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the correlation between secondhand smoke and CMs has been a concern for several decades, different studies obtained somewhat different results . Most studies reported a significantly increased risk for cardiovascular system malformations, whereas a study by Wasserman et al did not .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, study results regarding the association have been inconsistent. Some studies suggested that exposure to secondhand smoke in nonsmoking women significantly increases the risk of CMs in their offspring, whereas others showed no relation or even a protective effect . In 2010, two meta‐analyses were conducted to examine the association between secondhand smoke and CMs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for cleft lip and/or palate, which are the most frequent congenital craniofacial malformations. Cohort and case control studies have identified certain environmental factors as risk factors, including alcohol, smoking and excessive intake of vitamin A (DeRoo et al, ; Kummet et al, ; McKinney et al, ). One cohort study revealed that smoking during pregnancy is a risk factor for isolated CA (Kancherla et al, ).…”
Section: Amniotic Band Constrictionmentioning
confidence: 99%
“…In humans, plasma zinc concentration (PZn) is affected by many factors such as smoking, drinking alcohol, diabetes, and drug consumption such as 6‐mercaptopurine, thalidomide, and valproic acid (Uriu‐Adams & Keen, ). However, there is no consensus between plasma zinc status in pregnant women and the risk of NSCL/P in their offspring (Hozyasz et al, ; Krapels et al, ; McKinney et al, ; Munger et al, ; Shaw, Carmichael, Laurent, & Rasmussen, ; Tamura et al, ). Ideally, in order to evaluate this association, maternal zinc levels should be analyzed at the critical time of lip and primary palate formation is around six weeks of gestational age (Mossey, Little, Munger, Dixon, & Shaw, ; Sperber, ).…”
Section: Introductionmentioning
confidence: 99%